Report on the Observance of Standards and Codes, Accounting and Auditing : Module B - Institutional Framework for Corporate Financial Reporting, B.3 Financial Sector - Banking - World Bank (World Bank, Washington, DC, 2017)
The purpose of this report is to gain an understanding of the financial reporting requirements for the banks in a jurisdiction in addition to or instead of the requirements for commercial enterprises in general. The term bank in this assessment is used to refer to institutions authorized to receive deposits and to lend money as defined by the legal framework in the jurisdiction. There are also questions in relation to the monitoring and enforcement capacity of the local banking supervisor in respect of financial reporting of banks specifically. Questions are based on the internationally-recognized core principles for effective banking supervision issued by the Basel Committee on banking supervision, in particular Principle 27 Financial reporting and external audit. The questionnaire is structured as follows: overview of the banking sector; financial reporting requirements for Banks; statutory audit and other forms of independent assurance; audit committees; filing and publication of financial statements; monitoring and enforcement: financial reporting; and corporate governance.